Scoping review of balanced scorecards for use in healthcare settings: development and implementation - Nicole Spencer; Diane Lacaille; Victoria Bohm; Claire EH Barber (BMJ Open Quality)
Objective Balanced scorecards (BSCs) were developed in the early 1990s in corporate settings as a strategic performance management tool that emphasised measurement from multiple perspectives. Since their introduction, BSCs have been adapted for a variety of industries, including to healthcare settings. The aim of this scoping review was to describe the application of BSCs in healthcare.Methods Medline, Embase and CINHAL databases were searched using keywords and medical subject headings for ‘balanced scorecard’ and related terms from 1992 to 17/04/2020. Title and abstract screening and full text review were conducted in duplicate by two reviewers. Studies describing the development and/or implementation of a BSC in a healthcare setting were included. Data were abstracted using pilot-tested forms and reviewed for key themes and findings.Results 8129 records were identified and 841 underwent a full text review. 87 articles were included. Over 26 countries were represented and the majority of BSCs were applied at a local level (54%) in hospital settings (41%). While almost all discussed Kaplan and Norton’s original BSC (97%), only 69% described alignment with a strategic plan. Patients/family members were rarely involved in development teams (3%) which typically were comprised of senior healthcare leaders/administrators. Only 21% of BSCs included perspectives using identical formatting to the original BSC description. Lessons learnt during development addressed three main themes: scorecard design, stakeholder engagement and feasibility.Conclusions BSC frameworks have been used in various healthcare settings but frequently undergo adaptation from the original description in order to suit a specific healthcare context. Future BSCs should aim to include patients/families to promote patient-centred healthcare systems. Considering the heterogeneity evident in development approaches, methodological guidance in this area is warranted.